Testing Different Models for the Rotation Curve of the Milky Way Using BURT Observations - H. Azeez, Jazeel; S. Mahdi, Hareth; Umar, Roslan; M. Abood, Kamal (Al-Nahrain Journal of Science, 2026)
Understanding the rotation curves (RCs) of our Milky Way galaxy represents a main tool to understand its dynamical evolution and the connection between different regions in the galaxy. The present work is intended to test the applicability of three rotation curve models against two datasets, the first being the well-known Sofue data, and the second being the Baghdad University Radio Telescope (BURT) data, both for the HI 21-cm emission line. The tested models are the Time of Events (ToE) model, the Brandt model, and the Navarro-Frenk-White (NFW) model. The fitting results showed that the ToE model provided the best prediction for the experimental data compared to the other two models for both BURT and Sofue data within all regions in the galaxy. The other two models applied slightly well only in the central region, while their results diverge near the edge region. The reduced R2 values that ​​we obtained for BURT and Sofue data are equal to 0.79 and 0.94, respectively. In addition, the ToE model worked as a calibration tool for the BURT data point, which can predict the behavior of the rotation curve and fill in the gaps of the missing points in the observed BURT data.